THE EFFECTIVENESS OF THE TAHFIDZ AL-QUR'AN PROGRAMME IN IMPROVING STUDENT DISCIPLINE AND ACADEMIC ACHIEVEMENT - Amal Fathullah; Muhammad Nur Effendi; Muhammad Yusuf (Adisam Publisher, 2025)
The Effectiveness of the Qur'anic Tahfidz Programme in Improving Students' Academic Discipline and Achievement refers to the integral benefits that a structured programme in memorising the Qur'an brings to the improvement of students' personal discipline as well as learning achievement. The programme not only facilitates students' mastery of religious content, but also leads them to adopt regular and systematic study habits, which has a direct impact on improving their academic performance. The research method used in this study was literature review. The results of the literature review showed that students involved in the Tahfidz Al-Qur'an Programme showed significant improvements in self-discipline and academic performance. The discipline applied in following a structured study schedule regularly correlates positively with the level of concentration and learning efficiency in other academic subjects. Furthermore, intensive memorisation improves students' memory function and concentration, which directly supports their capacity to retain and process academic information. The study also found that there was an increase in positive attitude towards learning and a more general increase in motivation among students who participated in the Tahfidz programme.